(untitled) (Archives of Pediatrics of Uruguay, 2022)
Improvements in the populations’s quality of life and medical progress have contributed to the increase of survival rates of children and adolescents, as well as to a progressive rise in children with chronic, complex diseases or health conditions, dependent on medical devices and / or technology, who live with the possibility of life-threatening complications. This situation brings multiple challenges in the decision-making processes regarding the relevance and proportionality of diagnostic, therapeutic and monitoring measures, considering the real benefit and / or the burden that they can cause in the quality of life of the child and his family. In recent years, within the framework of health care, the concepts and procedures of advanced care planning and limitation or adequacy of therapeutic effort (ATE) have been incorporated. The aim of this paper is to describe the basic definitions needed to understand and implement ATE processes, the bioethical and legal framework for such processes, the procedure for the implementation of the definition of Directives for the Adequacy of Therapeutic Effort (DATE), prepared by the Pediatric Palliative Care Unit of the Pereira Rossell Hospital Center.